2017
DOI: 10.1371/journal.pone.0170454
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Genotoxic and Mutagenic Activity of Organic Extracts from Drinking Water Sources

Abstract: An increasing number of industrial, agricultural and commercial chemicals in the aquatic environment lead to various deleterious effects on organisms, which is becoming a serious global health concern. In this study, the Ames test and SOS/umu test were conducted to investigate the potential genotoxicity and mutagenicity caused by organic extracts from drinking water sources. Organic content of source water was extracted with XAD-2 resin column and organic solvents. Four doses of the extract equivalent to 0.25,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 41 publications
(45 reference statements)
1
17
0
Order By: Relevance
“…Furthermore, the effects of water sample C on A. cepa cells and root growth in this study may logically be expected in the crops (along the River bank) that are being watered with water from the sampling point C through bioaccumulation and biomagni cation. These effects may be further transferred to consumers of these crops including humans along the food chain as reported by Guan et al [1]. This extrapolation of the outcomes of this study to predict similar effects in animal cells is based on the fact that there is oxidase enzyme in A. cepa cells which makes it suitable to evaluate genotoxicity of promutagens which requires conversion to mutagenic or genotoxic metabolites, although at a lesser rate compared to how it is carried out by P-450 enzyme in the liver cells of higher animals.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Furthermore, the effects of water sample C on A. cepa cells and root growth in this study may logically be expected in the crops (along the River bank) that are being watered with water from the sampling point C through bioaccumulation and biomagni cation. These effects may be further transferred to consumers of these crops including humans along the food chain as reported by Guan et al [1]. This extrapolation of the outcomes of this study to predict similar effects in animal cells is based on the fact that there is oxidase enzyme in A. cepa cells which makes it suitable to evaluate genotoxicity of promutagens which requires conversion to mutagenic or genotoxic metabolites, although at a lesser rate compared to how it is carried out by P-450 enzyme in the liver cells of higher animals.…”
Section: Discussionmentioning
confidence: 90%
“…Rivers, lakes and ponds are sources of freshwater providing water for drinking, irrigating farmlands and other human activities globally. Pollution of surface water source occurs through release of industrial wastewater, agricultural and domestic wastes into water body according to Guan et al [1] Hussein et al [2] observed that contamination and pollution of aquatic environment has become a serious matter of concern globally due to their adverse effects on the ecological balance including loss of aquatic biodiversity. Although natural contamination of freshwater sources may occur at gradual processes through chemical weathering and soil leaching, but the release from anthropogenic sources is rapid and takes place at alarming rate as reported by Ogunkunle et al [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many mutagenic/genotoxic substances can be present and accumulate in the aquatic and soil environments, and have adverse effects on biocenosis and can affect humans through drinking water (Ceretti et al, 2016;Guan et al, 2017), surface water (Ohe, Watanabe, & Wakabayashi, 2004) and the food chain (Hamilton, Young, Bailey, & Watts, 2018). Consequently, the diffusion of these substances in water and soil could became a public health problem (Drzeżdżon, Jacewicz, & Chmurzyński, 2018;Rashtian, Chavkin, & Merhi, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Waste oil, which is the main pollutant in the oil refinery and in petrochemical wastewater, forms a layer on the receiving water body surface, interfering with oxygenation of the water body, as well as producing a photochemical pollution that increases the chemical oxygen demand (COD). A high COD, when related to industrial oil wastes, can lead to mortality of aquatic life forms and when in drinking water can cause increased activity of mutagenic and carcinogenic in humans (Guan et al 2017). To protect the environment and maintain good water quality, industrial wastewaters are treated by purification, removing sediment, and separation of water from the oil.…”
Section: Introductionmentioning
confidence: 99%